A study on thermoelectric technology application in net zero energy buildings. (15th October 2016) - Shen, Limei; Pu, Xiwang; Sun, Yongjun; Chen, Jiongde
Abstract: Net Zero Energy Building (NZEB) has gained increasingly wide attentions over last few years and net zero energy starts to become a new design target of future buildings. This paper presents the first study on thermoelectric technology applications in NZEBs in which both thermoelectric cooling and thermoelectric generation are adopted. Substituting conventional air-conditioning system, the thermoelectric radiant ceiling and the thermoelectric primary air handling unit are adopted to provide thermal comfort and fresh air in NZEBs. Meanwhile, the thermoelectric generation is employed to improve the solar energy generation. Case studies have been performed to investigate the application feasibility of the proposed thermoelectric systems by evaluating the annual energy balance. The study results show that the thermoelectric cooling is able to supply sufficient cooling and heating to ensure thermal comfort. Moreover, the thermoelectric generation significantly improves the annual solar energy generation by 767 kWh (34%) in comparison with conventional photovoltaic system, which eventually turns the targeted office building from a non-zero energy building to a plus energy building. This study provides a new way to apply thermoelectric technology in NZEBs which directly lead to benefits including zero Freon, simple piping, and quiet and reliable operations. Highlights: The application of thermoelectric technology in NZEBs is introduced. The annual energy balance of the novel system is analyzed. COP of TEC system could be comparable to conventional HVAC systems. The annual energy generation enhancement of solar TEG system is 34%.